Trap-assisted monolayer ReSe2/Si heterojunction with high photoconductive gain and self-driven broadband photodetector. - Jo, Beomsu; Seo, Kanghoon; Park, Kyumin; Jeong, Chaewon; Poornaprakash, Bathalavaram; Lee, Moonsang; Ramu, Singiri; Hahm, Myung Gwan; Kim, Young Lae (Frontiers in Materials, 2024)
We fabricated an ambipolar photodiode using monolayer triclinic ReSe2, synthesized by chemical vapor deposition on p-type Si substrate. The photodetector has a broadband response range from 405 to 1100 nm. The device exhibits high sensitivity to NIR radiation with a high Iph/Idark (ON/OFF) ratio of 5.8 × 10 4 , responsivity (R) of 465 A/W, and specific detectivity (D) of 4.8 × 10 13 Jones at open circuit voltage (Voc), indicating photovoltaic behavior. Our ReSe2/Si heterojunction photodetector also exhibits low dark current of 1.4 × 10 -9 A and high external quantum efficiency (EQE) of 54368.2% for 1060 nm at -3 V, demonstrating a photoconductive gain. The maximum responsivity (R = 465 A/W) can be achieved at -3 V reverse bias under 1060 nm. The device has a high ideality factor (4.8) and power coefficient (α = 0.5), indicating the presence of interface and sub-gap states that enhance device responsivity at lower illumination intensities by re-exciting trapped carriers into the conduction band. Our results offer important insights into the underlying photo-physics of ReSe2/Si heterojunction and suggest promising avenues for developing advanced photodetectors.